2016
DOI: 10.1175/jas-d-16-0069.1
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Atmospheric Gravity Waves and Large-Scale Flows: An Efficient Description beyond the Nonacceleration Paradigm

Abstract: With the aim of contributing to the improvement of subgrid-scale gravity wave (GW) parameterizations in numerical weather prediction and climate models, the comparative relevance in GW drag of direct GW–mean flow interactions and turbulent wave breakdown are investigated. Of equal interest is how well Wentzel–Kramer–Brillouin (WKB) theory can capture direct wave–mean flow interactions that are excluded by applying the steady-state approximation. WKB is implemented in a very efficient Lagrangian ray-tracing app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 49 publications
5
49
0
2
Order By: Relevance
“…The need for transience and a move away from the single column approach are crucial for improving these schemes. The results in this paper support the conclusions of Senf and Achatz (), Ribstein et al (), and Bölöni et al () who found that using ray tracing techniques with WKB theory to include time dependence and horizontal propagation led to much better agreement with large eddy simulations models on wave‐mean flow interactions. It is noted that typical operational parameterizations work statistically and consider a broad spectrum of waves.…”
Section: Discussionsupporting
confidence: 88%
“…The need for transience and a move away from the single column approach are crucial for improving these schemes. The results in this paper support the conclusions of Senf and Achatz (), Ribstein et al (), and Bölöni et al () who found that using ray tracing techniques with WKB theory to include time dependence and horizontal propagation led to much better agreement with large eddy simulations models on wave‐mean flow interactions. It is noted that typical operational parameterizations work statistically and consider a broad spectrum of waves.…”
Section: Discussionsupporting
confidence: 88%
“…Additional processes that may lead to GW dissipation are radiative and turbulent damping (e.g., Marks and Eckermann, 1995). Even without dissipation GWs may exchange momentum and energy with the background wind, by either horizontal refraction (Buehler and McIntyre, 2003;Preusse et al, 2009) or transient nonlinear interactions (Sutherland, 2006;Muraschko et al, 2015;Boeloeni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Being mainly excited in the troposphere by flow over terrain, by convection, or by spontaneous emission, GWs may propagate both vertically and horizontally over large distances to deposit their momentum and energy far away from their source upon instability or transience (e.g., Fritts and Alexander, 2003;Sato et al, 2009Sato et al, , 2012Preusse et al, 2009;Bölöni et al, 2016). Thus, GWs are an important mechanism that couples the middle and upper atmosphere to the troposphere (e.g., Lübken et al, 2010, and references therein).…”
Section: Introductionmentioning
confidence: 99%